Metal oxide surge arrester trending and analysis - Lotepi, Nor'aini (2015)
Surge arrester is very important and is required for the insulation coordination of to power system equipment. It will regulate the rising voltage in power system in order not to exceed the withstand voltage levels of equipment. A good arrester should return to its original condition after its voltage-limiting operation. A reliable condition monitoring of surge arrester is important to ascertain the continuity and reliability of power supply. The effect or behaviour of the different surge arrester used, environmental effects on the surge arrester and trending analysis on surge arrester need to be considered in order to record and establish database. The database of the surge arresters were recorded in order to analyse the trending of the arrester. The recorded data was analysed using the MATLAB. Based on the third harmonics current measurements, the arrester types are ranked from the best third harmonic current to the worse third harmonic current. Arrester type Siemens is found to be the best arrester based on its very low leakage current increment with number of years in service.